Whole Grain Intake Is Prospectively Associated with Lower Gain in Abdominal Obesity over 18 Years of Follow-up (OR33-04-19). (13th June 2019) - Sawicki, Caleigh; Rogers, Gail; Jacques, Paul; Livingston, Kara; McKeown, Nicola
Abstract: Objectives: Abdominal adiposity has been associated with greater risk of metabolic and cardiovascular diseases independent of overall BMI. Prospective studies examining the relationship between whole grain (WG) and refined grain (RG) consumption and abdominal adiposity are scarce. We examined the prospective relationship between WG and RG consumption and both weight and waist circumference (WC), a surrogate marker of abdominal adiposity, over 18 years of follow-up. Methods: Subjects were participants in the Framingham Offspring cohort (3514 subjects with 13, 864 unique observations) with mean baseline age of 54.2 years (SE = 0.16) and mean BMI of 27.3 kg/m 2 (SE = 0.11). Diet, health, and lifestyle data were collected approximately every 4 years up to 5 times over a total median of 18 years of follow-up. Dietary information was assessed using a semi-quantitative food-frequency questionnaire. WG intake was estimated in grams per day and grouped into pre-determined categories (≤8 g/d, 8–16 g/d, 16–24 g/d, and 24+ g/d). RG intake was estimated in servings per day and grouped into quartiles. Annualized change in weight and WC was examined using mixed models accounting for repeated measures. Results: WG intake ranged from a median of 4.5 g/d in the lowest category to 34.3 g/d in the highest category. After adjustment for demographic and lifestyle factors, greater WG intake was associated with less four-year gain in WC, with those in the highest category gaining (mean ± SE) 1.77 ± 0.08 cm in WC compared to 2.86 ± 0.12 cm in the lowest category ( P -trend < 0.001). Conversely, greater RG intake was associated with greater four-year gain in WC. Those in the highest quartile (median intake of 4.3 servings/d) gained more (2.82 ± 0.12 cm gain in WC) compared to the lowest quartile (median intake of 1.2 servings/d) (1.66 ± 0.1 cm gain in WC). These associations remained significant even when subjects were stratified by baseline BMI or WC. WG intake was not associated with 4-year change in overall body weight after adjusting for lifestyle factors. However, RG intake was associated with greater 4-year gain in body weight among overweight or abdominally obese subjects. Conclusions: Greater WG intake and less RG intake is prospectively associated with less gain in WC. Replacing RG foods with WG equivalents may be an effective dietary modification to attenuate abdominal weight gain and reduce the risk for cardiometabolic disease. Funding Sources: NIH/NHLBI(Contract N01-HC-25195), USDA (Agreement No. 58-1950-4-003), and General Mills Bell Institute of Health and Nutrition.